Building rehabilitation study-towards providing guidelines for heritage institutional building of Malaysia. Case study : Universiti Pendidikan Sultan Idris / Mohd Fuad Eshak - Eshak, Mohd Fuad (2011)
Institute of Higher Education is one proof that the education system has expanded over the years. This development starts from a school, college, institution up to a university. This development process began when the British government to provide education to the local community at that time. Planning the development of higher education institutions are also experiencing the process and influenced by elements of the British cuisine. The development of colonial schools in Malaysia which was built during British rule have been documented by many writers, historians and academics. However, the documentation of buildings colonial in higher education is less emphasized. There is no guarantee for the uniqueness and authenticity of the colonial buildings at higher education institutions will be preserved. At this time, the colonial structure in higher education is still used as places of learning and teaching. However, maintenance and management of historic buildings is still at a low level of awareness. Lack of awareness has caused the improvements to continue the colonial buildings have no control and guidelines, especially the colonial building that has not been enacted. Colonial Building in Institutions of Higher Learning which has been gazetted as a national heritage building must comply with the National Heritage Act. This study will identify problems in the use of colonial buildings Universiti Pendidikan Sultan Idris (UPSI), and suggests some guidelines and references for the conservation of colonial buildings which are not gazetted as a national heritage building in the program. Policies and Guidelines to be provided is general and specifically on an analysis of the buildings that have been conducted on UPSI campus. This analysis is not only based on the design and use, but affect the technical aspects, policies and guidelines, with reference to the National Heritage Act and other references. Also conducted interviews with the conservator to seek views on the study. Policy and guidelines will become the future reference for other institutions of higher learning.